Superoxide- and no-dependent mechanisms of antitumor and antimetastatic effect of L-arginine hydrochloride and coenzyme Q₁₀ - Burlaka, A.P.; Ganusevich, I.I.; Golotiuk, V.V.; Vovk, A.V.; Lukin, S.M. (Experimental Oncology, 2016)
Aim: To study the redox-dependent mechanism of antiradical, antitumor and antimetastatic action of L-arginine hydrochloride (L-Arg) and coenzyme Q₁₀ (CoQ₁₀) in vivo. Materials and Methods: The study was performed on С57Вl mice with transplanted Lewis lung carcinoma treated by intraperitoneal injections of L-Arg at low or high doses (60 and 360 mg/kg body weight), CoQ₁₀ (0.2 and 1.2 mg/kg body weight) or their combinations. Electron paramagnetic resonance was applied for analysis of mitochondrial electron transport chain, СoQ₁₀ levels, free iron (FI), the level of NO, and the rate of superoxide radical generation. The activity of matrix metalloproteinase (MMP)-2 and -9 in tumor tissue was determined by zymography method in polyacrylamide gel. Results: Administration of L-Arg at high doses caused an inhibition of tumor growth by 48 ± 8.0%, increase of superoxide radical generation rate and NO levels to a value of 1.23 ± 0.14 аnd 2.26 ± 0.31 nm/g tissue · min, and decreased activity of MMP-2 and -9 (3.55 ± 0.8 and 4.8 ± 1.0 r.u., respectively). Treatment with L-Arg at low doses stimulated tumor growth and increased the levels of MMP-2 and -9 activities (8.44 ± 2.7 and 9.8 ± 3.1 r.u., respectively). Administration of СoQ₁₀ at high doses significantly decreased superoxide radical generation rate to the values of 0.44 ± 0.09 nm/g tissue · min, levels of free iron and NO, and caused tumor growth inhibition by 54 ± 11.3%. The combined use of L-Arg and СoQ₁₀ at high doses caused tumor growth inhibition by 51 ± 7.4% compared to Lewis lung carcinoma-bearing untreated animals (р < 0.05). Conclusions: Administration of L-Arg and СoQ₁₀ caused the dose-dependent effect on the rate of generation of superoxide radicals, level of ubisemyquinone, complexes NOFeS-proteins, levels of FI and NO. L-Arg at low doses positively modulated MMP-9 activity that promoted tumor progression. Upon combined use of L-Arg and СoQ₁₀, superoxide radicals and NO form the redox state that causes decrease of MMP-2, -9 activities with consequent inhibition of tumor invasion and metastasis.